The politics of discipleship: becoming postmaterial citizens - Ward, Graham (The church and postmodern culture, 2009)
Introduction -- Section 1: The world -- Democracy : crisis and transformation -- Globalization : when the world is not enough -- Postsecularity : the new visibility of religion -- Section 2: The church -- Theological introduction -- The city and the struggle for its soul -- The metaphysics of the body -- The politics of election and of following